Elastyczność jako metakompetencja organizacji - Osbert-Pociecha, Grażyna (Flexibility as a meta competence of organization, 2007)
This article refers to recommendations for contemporary organization. They often exist in both academic and practical literaturę. They usually order organization to be both flexible (dynamie) and competent, so the author madę an attempt to explor the relationship between these imperatives of organization.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (5); 2007; nr 1187, s. 33-42